Why Is the Crowd Divided? Attribution for Dispersion in Online Word of Mouth - He, Stephen X.; Bond, Samuel D. (Journal of Consumer Research, 2015)
Abstract The widespread availability of online word of mouth (WOM) enables modern consumers to assess not only the opinions of others about products and services, but also the extent to which those opinions are consistent or dispersive. Despite longstanding calls for greater understanding of mixed opinions, existing evidence is inconclusive regarding effects of WOM dispersion, and theoretical accounts have relied primarily on the notion of reference dependence. Extending prior work, this research proposes an attribution-based account, in which consumer interpretation of WOM dispersion depends on the extent to which tastes in a product domain are perceived to be dissimilar, so that dispersion can be attributed to inconsistency in reviewer preferences rather than the product itself. Across four experimental studies, participants presented with online rating distributions were more tolerant of dispersion in taste-dissimilar product domains than taste-similar product domains, and the difference was driven by underlying attributions. Together, these findings expand current understanding of WOM, social distributions, and risk perception, by revealing distinct pathways through which consumers respond to differences of opinion. In addition, they suggest the opportunity to proactively influence the manner in which dispersion is perceived, highlighting its positive connotations while diminishing its association with risk.